Brain serotonergic and dopaminergic modulators, perceptual responses and endurance exercise performance following caffeine co-ingested with a high fat meal in trained humans - Hadjicharalambous, M. P.; Kilduff, L. P.; Pitsiladis, Y. P. (Journal of the International Society of Sports Nutrition, 2010)
The present study examined putative modulators and indices of brain serotonergic and dopaminergic function, perceptual responses, and endurance exercise performance following caffeine co-ingested with a high fat meal.